HUBUNGAN KETERAMPILAN MENYIMAK BERITA DENGAN KETERAMPILAN MENULISKAN KEMBALI BERITA SISWA KELAS VII SMP NEGERI 1 LUBUK ALUNG - Setiawati, Fenny Wulandari; Nursaid, Nursaid; Noveria, Ena (Universitas Negeri Padang, 2016)
ABSTRACTÂ This article is written to discuss the results of research on the relationship of listening skills with skills rewriting news news seventh grade students of SMP Negeri 1 Lubuk Alung. Data of this research is the result of listening skills scores news and scores the results of rewriting news skills tests. The data was obtained through two types of test, which is an objective test for measuring the listening skills of news and performance tests for skills rewriting news. This type of research is quantitative descriptive method. The results of this research are three: (1) news listening skills class VII SMP Negeri 1 Lubuk Alung are in good qualification at 81.08. (2) the skill rewriting overall student news at 81.53 and are on good qualification, and (3) based on the t-test, the alternative hypothesis (H1) is accepted at 95% significance level and degrees of freedom (df) = n-1 because thitungÂ¬> ttabel (10.75> 1.68).Â Kata kunci : hubungan, minyimak, menulis, berita